Cytokine profile in quadriceps muscles of patients with severe COPD. Issue 2 (17th September 2007) - Barreiro, E; Schols, A M W J; Polkey, M I; Galdiz, J B; Gosker, H R; Swallow, E B; Coronell, C; Gea, J
Abstract : Background: Systemic proinflammatory cytokines and oxidative stress have been described in association with peripheral muscle wasting and weakness of patients with severe chronic obstructive pulmonary disease (COPD), but their expression in skeletal muscle is unknown. The objectives of the present study were to determine muscle protein levels of selected cytokines in patients with COPD and to study their relationships with protein carbonylation as a marker of oxidative stress, quadriceps function and exercise capacity. Methods: We conducted a cross sectional study in which 36 cytokines were detected using a human antibody array in quadriceps specimens obtained from 19 patients with severe COPD and seven healthy controls. Subsequently, selected cytokines (tumour necrosis factor (TNF)α, TNFα receptors I and II, interleukin (IL) 6, interferon γ, transforming growth factor (TGF) β and vascular endothelial growth factor (VEGF)), as well as protein carbonylation (oxidative stress index) were determined using an enzyme linked immunosorbent assay (ELISA) in all muscles. Results: Compared with controls, the vastus lateralis of patients with COPD showed significantly lower protein ELISA levels of TNFα, which positively correlated with their quadriceps function, TNFα receptor II and VEGF. Protein ELISA levels of IL6, interferon γ and TGFβ did not differ between patients and controls. Quadriceps protein carbonylation was greater in patients and inversely correlated with quadriceps strength among them. Conclusions: These findings do not support the presence of a proinflammatory environment within the quadriceps muscles of clinically and weight stable patients with severe COPD, despite evidence for increased oxidative stress and the presence of muscle weakness.